Problem-Based Physical Learning with Experimental and Demonstration Methods : Analysis with Scientific Attitude and Student Creativity - Pujiarto, Lulus (Yayasan Darussalam Bengkulu, 2022)
This study aims to determine the existence of: 1) the effect of Experimentation and Demonstration methods on physics learning achievement, 2) the effect of scientific attitudes on physics learning achievement, 3) the effect of creativity on physical learning achievement, 4) the interaction of learning methods and scientific attitude on physics learning achievement , 5) the interaction of learning methods and creativity on physics learning achievement, 6) the interaction of scientific attitude and creativity on physics learning achievement, 7) the interaction of learning models, scientific attitude, and creativity on physics learning achievement. This research was conducted in December 2009 - May 2010 using the Experimental and Demonstration method. The population of this study were all grade X students of SMA Negeri I Mejayan in the 2009/2010 school year. The sample in this study were four classes taken at random (cluster random sampling). Classes that use experimental methods are selected classes X-1 and X-3 and classes that use selected demonstration methods are classes X-6 and X-7. Variable data collection techniques are used to collect data on cognitive learning achievement, while scientific attitudes and student creativity are obtained using the questionnaire and observation methods. Research hypothesis testing using ANAVA three cell path is not the same as the help of Minitab software 15. The results of research data analysis are 1) there is an influence of the use of Experimentation and Demonstration methods on physics learning achievement, the experimental method is better than the demonstration method (p-value = 0,000 <0.050 ), 2) there is an effect of high and low scientific attitudes of students on physics learning achievement, students who have high scientific attitudes have better achievements than students whose scientific attitude is low (pvalue = 0,000 <0.050), 3) there is an influence of high and low creativity of students towards physics learning achievement, students who have high creativity are better than students with low creativity (p-value 0,000 <0.050), 4) there is no interaction between learning methods and students' scientific attitudes toward physics learning achievement (p value = 0.433> 0.050) 5 ) there is no interaction between learning methods and student creativity on physics learning achievement (p-val ue = 0.251> 0.050), 6) there is no interaction between scientific attitude and student creativity on physics learning achievement (p-value = 0.180> 0.050, 7) there is an interaction between learning methods, scientific attitude, and student creativity on physics learning achievement ( p-value = 0.018 <0.050).